2008
DOI: 10.1086/589108
|View full text |Cite
|
Sign up to set email alerts
|

Stratification, Composition, and Function of Marine Mammal Blubber: The Ecology of Fatty Acids in Marine Mammals

Abstract: This study of vertical fatty acid profiles, based on analysis of 58 fatty acids sampled at 3-mm intervals throughout the blubber column of a model marine mammal, the ringed seal (Pusa hispida), revealed three chemically distinct layers. The average depths of the outer and inner layers were quite consistent (approximately 1.5 and approximately 1 cm, respectively). Consequently, the middle layer varied greatly in thickness, from being virtually absent in the thinnest animals to 2.5 cm thick in the fattest. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 37 publications
5
90
1
Order By: Relevance
“…Earlier studies reported that fatty acid mobilisation during fasting in seals occurred principally from the inner blubber layer, while the outer part remained more stable (Strandberg et al, 2008). However, in the present study, we observed a slight but significant decrease in lipid content in the outer layer as well.…”
Section: Variations In Concentrationscontrasting
confidence: 75%
“…Earlier studies reported that fatty acid mobilisation during fasting in seals occurred principally from the inner blubber layer, while the outer part remained more stable (Strandberg et al, 2008). However, in the present study, we observed a slight but significant decrease in lipid content in the outer layer as well.…”
Section: Variations In Concentrationscontrasting
confidence: 75%
“…Marine mammal blubber reflects the diet composition and dietary intake of prey over a period of weeks to months (Iverson et al, 1995. Vertical stratification of FAs in the blubber layer of marine mammals has been documented in pinnipeds (Best et al, 2003;Thiemann et al, 2004) and cetaceans (Thiemann et al, 2008;Strandberg et al, 2008), although the degree of stratification appears to be less in larger cetaceans (Hooker et al, 2001;Koopman, 2007). In general, the outer blubber layer is composed of a larger proportion of biosynthesized components and MUFAs less than 18 carbons in length than the inner blubber layer, which is more metabolically active and contains greater amounts of MUFAs with 18 carbons or more, non-branched saturated FAs (SFAs), and PUFAs (Koopman et al, 1996;Smith and Worthy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is a complex tissue with diverse and overlapping roles. The fact that blubber differs in biochemical composition and in function along the body and its depth (Lockyer et al, 1984;Strandberg et al, 2008;Zeng et al, 2015), means that its relationship with overall energy stores may asymptote in order to service these ancillary functions. This is particularly the case for measurements obtained from the outer blubber layer which has been shown to be the most stable and the least active into the lipid dynamic (Ackman et al, 1975b;Aguilar and Borrell, 1990;Lockyer et al, 1984), such as those obtained by shallow biopsy.…”
Section: Discussionmentioning
confidence: 99%